Progression to Stage 4 chronic kidney disease and death, acute kidney injury and hospitalization risk: a retrospective cohort study. Issue 7 (20th November 2015) - Sud, Maneesh; Tangri, Navdeep; Pintilie, Melania; Levey, Andrew S.; Naimark, David M.J.
Abstract : Background: Chronic kidney disease (CKD) Stage 4 is on the path to kidney failure, but there is little information on the risks associated with progression to Stage 4 per se . The objective of this study is to determine how progression from Stage 3 to Stage 4 CKD alters morbidity and mortality in a referred cohort of patients. Methods: We conducted a retrospective cohort study consisting of 1607 patients with estimated glomerular filtration rate (eGFR) of 30–59 mL/min/1.73 m 2 referred to a nephrologist at a tertiary care center in Ontario, Canada, between January 2001 and December 2008. Interim progression from Stage 3 to Stage 4 chronic kidney disease was defined by two independent outpatient eGFR values <30 mL/min/1.73 m 2 . Death, acute kidney injury (AKI) and all-cause hospitalizations subsequent to Stage 4 progression, but prior to the development of end-stage renal disease (ESRD), ascertained from administrative databases. Results: The mean (standard deviation) baseline eGFR was 43 (8) mL/min/1.73 m 2 . Over 2.66 years (interquartile range: 1.42–4.45), 344 (21%) patients progressed to Stage 4, 47 (3%) developed ESRD, 188 (12%) patients died, 143 (9%) were hospitalized with AKI and 688 (43%) were hospitalized for any reason. Compared with patients who did not progress to Stage 4, those who did progress had significantly higher adjusted risks of death [hazard ratio (HR) = 2.56, 95% confidence interval (95% CI): 1.75–3.75], AKI (HR = 2.32, 95% CI: 1.44–3.74) and all-cause hospitalization (HR = 1.87, 95% CI: 1.45–2.42). Conclusions: Progression from Stage 3 to Stage 4 CKD is associated with increased risks of death, AKI and hospitalization prior to ESRD.